Surgical Versus Conservative Intervention for Acute Achilles Tendon Rupture: A PRISMA-Compliant Systematic Review of Overlapping Meta-Analyses. Issue 45 (November 2015) - Zhang, Hao; Tang, Hao; He, Qianyun; Wei, Qiang; Tong, Dake; Wang, Chuangfeng; Wu, Dajiang; Wang, Guangchao; Zhang, Xin; Ding, Wenbin; Li, Di; Ding, Chen; et al.
Abstract : Abstract: Although many meta-analyses comparing surgical intervention with conservative treatment have been conducted for acute Achilles tendon rupture, discordant conclusions are shown. This study systematically reviewed the overlapping meta-analyses relating to surgical versus conservative intervention of acute Achilles tendon rupture to assist decision makers select among conflicting meta-analyses, and to offer intervention recommendations based on the currently best evidence. Multiple databases were comprehensively searched for meta-analyses comparing surgical with conservative treatment of acute Achilles tendon rupture. Meta-analyses only comprising randomized controlled trials (RCTs) were included. Two authors independently evaluated the meta-analysis quality and extracted data. The Jadad decision algorithm was applied to ascertain which meta-analysis offered the best evidence. A total of 9 meta-analyses were included. Only RCTs were determined as Level-II evidence. The scores of Assessment of Multiple Systematic Reviews (AMSTAR) ranged from 5 to 10 (median 7). A high-quality meta-analysis with more RCTs was selected according to the Jadad decision algorithm. This study found that when functional rehabilitation was used, conservative intervention was equal to surgical treatment regarding the incidence of rerupture, range of motion, calf circumference, and functional outcomes, while reducing the incidence of other complications. Where functional rehabilitation was not performed, conservative intervention could significantly increase rerupture rate. Conservative intervention may be preferred for acute Achilles tendon rupture at centers offering functional rehabilitation, because it shows a similar rerupture rate with a lower risk of other complications when compared with surgical treatment. However, surgical treatment should be considered at centers without functional rehabilitation as this can reduce the incidence of rerupture.